Pharmaceutical analysis and aspects of the quality control of St. John's Wort products - Wild, Tracy Joy (Rhodes University, Faculty of Pharmacy, Pharmacy, 2003)
Most complementary medicines contain a multitude of chemical components, some of which are claimed to contribute to the biological activity of such products. Use of complementary medicines for preventative and therapeutic purposes is increasing rapidly worldwide. Unfortunately, although control of these products is essential to ensure quality, safety, and efficacy, the quality control of most herbal preparations is currently poor to non-existent, with little or no safety and efficacy data required to support the marketing and use of these products. The objective of this study was therefore to develop suitable analytical methods to qualitatively and quantitatively analyse the relevant components (rutin, isoquercitrin, hyperoside, quercitrin, quercetin, kaempferol, hypericin, pseudohypericin and hyperforin) in St John's Wort dosage forms for quality control purposes. A gradient HPLC method using a Luna 5Â·mCâ‚ â‚ˆ(2) 150 x 2.00mm internal diameter (i.d.) column and UV detection, was developed for the separation of six of the relevant flavonoid compounds in St John's Wort, namely rutin, isoquercitrin, hyperoside, quercitrin, quercetin and kaempferol. The development process involved a systematic investigation of gradient conditions, flow rate, and temperature. This method was subsequently applied to assay selected commercially available St John's Wort products. This system provided the necessary accuracy, precision and reproducibility and was associated with several advantages when compared to using standard bore (4.60 mm i.d.) HPLC columns. The method developed is currently the only known method that separates all six relevant flavonoids in a reasonable run time (less than 20 minutes). It is also one of the few methods that has sufficient separation between rutin, isoquercitrin and hyperoside. A qualitative method for the fingerprinting of flavonoid components was also developed, using capillary electrophoresis (CE). CE is a rapidly growing powerful analytical technique for the separation of charged compounds. Micellar electrokinetic chromatography (MEKC) is a very powerful electrophoretic technique that is capable of selectively resolving both neutral and ionic solutes in a single run. A MEKC method suitable for the separation and determination of various flavonoid constituents used as marker compounds in Hypericum perforatum was developed. Investigations into the effect of pH, ionic strength, applied voltage and capillary dimensions on separation were performed. The optimised method was then applied to qualitatively analyse various St John's Wort products on the market. This method was found to be advantageous in that it was simple, cost-effective, required minimal sample preparation and utilised very small quantities of sample. Due to the vast differences in chemical properties between the various marker and active components in St John's Wort, it was necessary to develop separate analytical methods for the flavonoids and for the other three relevant compounds (hypericin, pseudohypericin and hyperforin). An isocratic HPLC method using a Luna 5Â·mCâ‚ â‚ˆ(2) 150 x 2.00mm (i.d.) column and UV detection was developed for the separation of hypericin, pseudohypericin and hyperforin. The development process involved a systematic investigation of buffer molarity, mobile phase composition, pH, flow rate, and temperature. This method was subsequently applied to assay selected commercially available St John's Wort products on the South African market. This system also provided the necessary accuracy, precision and reproducibility, as well as the advantages associated with the use of a narrow bore column as opposed to the use of the more commonly used wider bore columns. This method was validated and used to quantitate these three compounds in various commercial St John's Wort products. By applying this method to liquid chromatography "“ tandem mass spectrometry (LC-MS-MS), qualitative analyses of the same products was performed to obtain confirmation of the quantitative HPLC results. Mass spectrometry is a powerful detection tool that is more selective and specific than many detection systems used with HPLC. Natural medicines usually constitute a multitude of constituents with much potential interference. In this regard LC-MS-MS is a powerful tool, with its ability to unequivocally identify target analytes regardless of the presence of interferences or complex matrices. ESI-MS-MS was used for the qualitative analysis of the content of the naphthodianthrones and hyperforin in the respective tablet products assayed with HPLC. LC-MS-MS analyses were performed in order to identify the constituents and to verify the specificity of the HPLC method. High inter-product and inter-batch variability was observed for all nine compounds assayed. These quantitative results were confirmed with the respective qualitative analyses. This study confirms the need for strict quality control of herbal medicinal products commercially available to consumers.
Keywords: Hypericum perforatum; Hypericum perforatum -- Analysis; Hypericum perforatum -- Therapeutic use; Hypericum perforatum -- Physiological effect; Flavonoids -- Analysis